Desain Praktis Beban Gempa Dasar Untuk Bangunan Di Lahan Basah Kabupaten Banjar Kalimantan Selatan - Tjitradi, Darmansyah; Eliatun, Eliatun; Khatimi, Khusnul; Karim, Abdul; Lestari, Della Dwi; Tjitradi, Aeron (Borneo Engineering : Jurnal Teknik Sipil, 2024)
Banjar Regency is a regency in the province of South Kalimantan which has an area of 4,688 km² and a population of 580,100 people at the end of 2023. Banjar Regency has a capital city located in Martapura sub-district and is included in the Banjar Bakula metropolitan area candidate. Although the Banjar Regency area is an area with minimal seismic and volcanic activity, it has wetlands/swamps with low bearing capacity/soft soil that has the potential to damage buildings due to the amplification of earthquake vibrations. According to earthquake data, South Kalimantan and Banjar Regency in particular have experienced several earthquakes such as 13-14 February 2024 Banjar Regency (M4.7, M3.3, and M4.1), 18 February 2024 Hulu Sungai Tengah Regency (M3.2) and 02 April 2024 Tabalong (2.8M). This study aims to develop a practical design graph of the basic earthquake load spectrum response at 20 building locations in the sub-districts of Banjar Regency, which is certainly very useful for the wider community, especially construction actors in designing buildings in the wetland areas of Banjar Regency. The results of this study indicate that the design earthquake spectrum response graph for all sub-districts in Banjar Regency has normal behavior, namely the softer the soil conditions or the higher the building risk category, the greater the basic earthquake force that works, and structural design parameters, equations and practical design graphs have been obtained to determine the magnitude of the basic earthquake load (V) based on the weight of the building (W), risk category and site class for Banjar Regency.